Inhibition of bio corrosion of steel coupon by sulphate reducing bacteria and Iron oxidizing bacteria using Aloe Vera (Aloe barbadensis) extracts - O.K. Agwa; D Iyalla; G.O. Abu (Journal of Applied Sciences and Environmental Management, 2017)
The inhibition of biocorrosion of steel coupons by sulphate reducing bacteria (SRB) and Iron oxidizing bacteria (IOB) using Aloe vera (Aloe barbadensis) extract was tested. The water sample revealed a heterotrophic bacterial count of 1.7x103 cfu/ml for the sulphate reducing bacteria and 4.1x103 cfu/ml for the Iron oxidizing bacteria. Biocorrosion inhibition test using Aloe vera extract was prepared with 50 % w/v stock solution at 10 %, 20 %, 40 % and 80 % (v/v) concentrations. An increase in acidity was observed in the fresh post gate medium after 7 days to 6.6 with a slight drop to 6.5 after 28 days in the setup with SRB. In contrast, the pH of the setups with IOB showed an increase in alkalinity from 6.8 in fresh Winogradsky medium to 7.4 after 7 days. The conductivity of SRB setup increased from 3150 μS/cm to 27100 μS/cm after 7 days and decreased to 200 μS/cm after 28 days. On the other hand, the IOB setup showed an increase in conductivity from 100 μS/cm to 2820 μS/cm after 28 days. The surfaces of the metal coupon used in the biocorrosion testing were slimy to touch, indicating possible biofilm production. The average corrosion rate from day 7 to day 28 for IOB and SRB are 6.606 mpy and 12.48 mpy respectively. The 80 % v/v concentration of Aloe vera extract gave the highest inhibition efficiency, ranging from 89 %-100 % for IOB and 66 %- 100 % for SRB. Aloe vera extract inhibited corrosion of steel coupons mediated by aerobic iron oxidizing bacteria and anaerobic sulphate reducing bacteria.